2019
DOI: 10.1080/17482631.2019.1588034
|View full text |Cite
|
Sign up to set email alerts
|

Previous breastfeeding difficulties: an existential breastfeeding trauma with two intertwined pathways for future breastfeeding—fear and longing

Abstract: Purpose : Experiencing breastfeeding difficulties poses a risk for early cessation of breastfeeding and decreases the likelihood of breastfeeding a future child. To further understand breastfeeding outcomes, the aim of this study is to explain the phenomenon of breastfeeding difficulties in order to understand how women’s previous experiences of breastfeeding difficulties relate to their decisions about future breastfeeding. Methods : A reflective lifeworld hermeneutical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
1
29
0
2
Order By: Relevance
“…It is then crucial to enhance maternal confidence in her own abilities, enabling mothers to get further insight into the lactation process and the peculiar characteristics of infant growth that often take place in spurts [16]. Within this context, it has to be underlined that a previous negative breastfeeding experience and difficulty negatively affect the likelihood of subsequent breastfeeding success, leading to a potential fear of breastfeeding secondary to prior breastfeeding trauma [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is then crucial to enhance maternal confidence in her own abilities, enabling mothers to get further insight into the lactation process and the peculiar characteristics of infant growth that often take place in spurts [16]. Within this context, it has to be underlined that a previous negative breastfeeding experience and difficulty negatively affect the likelihood of subsequent breastfeeding success, leading to a potential fear of breastfeeding secondary to prior breastfeeding trauma [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several determinants of breastfeeding have been described within a complex framework, including structural settings and individual factors that are involved at multiple levels [6]. Among the individual factors, the experience of breastfeeding difficulties greatly contributes to early breastfeeding cessation and causes mothers to be less likely to breastfeed a future child [7]. However, “breastfeeding difficulties” includes a wide range of different biological, psychological, and social factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Palmer et al (12) demonstrated that a previous negative breastfeeding experience may lead to a fear of breastfeeding, with mothers being less likely to breastfeed a future child. On the other hand, consistently with the findings of the present study, Wouk et al (10) reported that experiencing positive outcomes during breastfeeding is associated with a lower risk of introducing formula or solid foods by 6 months of infant's age.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers are more likely to be satisfied with their breastfeeding experience by 12 months of infants' age when they have experienced positive emotions at 2 months postdelivery (10). In turn, a positive breastfeeding experience favors breastfeeding (11) whereas a previous negative breastfeeding experience may lead to a fear of breastfeeding a next child (12). Furthermore, an early breastfeeding discontinuation may disrupt maternal breastfeeding expectations and/or cause a "breastfeeding grief, " which could undermine maternal emotional well-being and mother-infant relationship (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Women express the joy they experience while breastfeeding and share their struggles and emotional turmoil when they are unable to meet their own breastfeeding goals (Brown, 2018). Negative or ‘denialist’ attitudes towards breastfeeding are sometimes fuelled by individuals with negative personal experiences (Palmer, 2019), which often originate from disempowering interactions with healthcare systems (Brown, 2018). Researchers face complex challenges when discussing the health benefits of breastfeeding because, although advancing research on this topic will ultimately improve health for all mothers and infants, it also perpetuates a dialogue that can cause guilt among women who did not breastfeed.…”
Section: Barriers and Challenges To Breastfeeding And Human Milk Resementioning
confidence: 99%